The Study of Cultural Diversity and Acceptance in Modern Society - Duangde, Danai (Interdisciplinary Journal of Humanities Studies, 2025)
This article focuses on the study of cultural diversity and the importance of embracing differences in modern society. It begins with an analysis of fundamental concepts and principles of diversity, including an exploration of relevant theories such as multiculturalism and a comparison of approaches to managing diversity across different countries. The article also highlights the positive impacts of embracing diversity in social, economic, and educational dimensions, such as reducing conflicts, fostering a skilled and diverse workforce, and promoting open-minded learning. Furthermore, the article addresses critical challenges arising from exclusion and stereotyping, as well as issues of inequality related to race, religion, and gender. Global challenges, such as racial discrimination and religious conflicts, are also discussed. The article proposes strategies for promoting diversity through education, comprehensive policy development, the role of media, and the creation of spaces for dialogue among diverse groups.